PERAN PENDIDIKAN ISLAM DALAM MEMBENTUK KARAKTER SISWA BERDASARKAN PERSPEKSTIF FILSAFAT PERENIALISME - Ratna Liviani (STAI Asy-Syukriyyah, 2023)
The purpose of this study is to determine the role of Islamic education in shaping the character of elementary school students based on their inherent nature, in accordance with the perspective of perennialist philosophy. This research uses qualitative techniques with descriptive methods, based on the results of interviews, observations, and documentation at MI Hidayatul Istiqomah. MI Hidayatul Istiqomah is a school that implements the national curriculum by integrating Islamic teachings to respond to the challenges of the times and prepare students to pursue higher education. The findings of this study indicate that MI Hidayatul Istiqomah has a vision and mission that are aligned with the objectives of the madrasa to educate students' character based on their nature through the school curriculum adopting noble values that are still relevant today supported by the teacher's role in providing exemplary, and fostering Islamic culture. which upholds the moral values of students.